ХИМИЧЕСКИЙ СОСТАВ ГЛАВНЫХ МИНЕРАЛОВ РУД МЕСТОРОЖДЕНИЯ "АПАТИТОВОЕ" МУШУГАЙСКОГО РУДНОГО УЗЛА (МОНГОЛИЯ) - Андреев Г.В.; Хубанов В.Б. (My University, 2005)
The Apatite ore deposit occurs in South Mongolia; it has the pipe-shaped ore-body where were mapped three types of ores: 1) rich apatite, 2) apatite-pyroxene, and 3) apatite disseminated ones. The main minerals in their composition arc apatites, pyroxenes, garnets and biotite. Apatites are represented by intermediate varieties between fluorine- and hydroxyle-apatite, in all cases they have high contents of rare earth's and silica. The pyro-xenes are represented by salites with calcium contents higher then magnesium and iron ones, and minor contents of Ti, Al, Mn, Na. Garnets occur in apatite-pyroxene ores in quantity from 1 to 15 %; their composition is inter-mediate between melanite and grossular. Biotite occurs usually as singular grains, with its content elevated so-metimes up to 3 %. Its composition is close to the standard one, but with lower content of iron oxide and a higher one of magnesium. In the whole, its features allow to attribute it to the magnesium biotite species.
Keywords: 553.549